2014
DOI: 10.3329/jasbs.v39i2.17860
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive emotion regulation in children as related to their parenting style, family type and gender

Abstract: This study aimed to investigate whether cognitive emotion regulation in children varies with parenting style, family type and gender. Toward this end, cognitive emotion regulation and perceived parenting style of 206 school children were measured. Standard regression analyses of data revealed that the models were significant and explained 17.3% of the variance in adaptive emotion regulation (Adjusted R²=0.173; F=9.579, p<.001), and 7.1% of the variance in less adaptive emotion regulation (Adjusted R²=.071, F=… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 23 publications
4
12
0
Order By: Relevance
“…Our findings also indicate an association of reappraisal with authoritative parenting, as expected (Karim et al, ). Although research into the association between parenting styles and emotion regulation is scarce, evidence from the field of emotional intelligence consistently supports the connection between the experience of authoritative parenting and the application of functional emotion regulation (see Argyriou, Bakoyannis, & Tantaros, , for an analysis).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings also indicate an association of reappraisal with authoritative parenting, as expected (Karim et al, ). Although research into the association between parenting styles and emotion regulation is scarce, evidence from the field of emotional intelligence consistently supports the connection between the experience of authoritative parenting and the application of functional emotion regulation (see Argyriou, Bakoyannis, & Tantaros, , for an analysis).…”
Section: Discussionsupporting
confidence: 92%
“…Specifically, when it comes to the use of specific emotion-regulation strategies, people who have experienced permissive or authoritarian parenting when they were children seem to have a preference for suppression (Jaffe, Gullone, & Hughes, 2010;Monzon, 2016). On the contrary, those who have experienced authoritative parenting prefer the more beneficial use of cognitive reappraisal (Jaffe et al, 2010;Karim, Sharafat, & Mahmud, 2014).…”
mentioning
confidence: 99%
“…Experiment 3 examined the role of parenting authority styles in the response to microexpressions in adults. Previous studies showed that an authoritative parenting style was a predictor of good adaptive emotion regulation in children aged 12 to 15 years, whereas an authoritarian parenting predicted less adaptive emotion regulation (Karim, Sharafat, & Mahmud, 2013). Moreover, the high parental control common in authoritarian parents is associated with poor emotional regulation and internalised (i.e., anxiety, depression) as well as externalised (i.e., delinquency, aggression) problems in adolescents (Barber, 1996; Bean, Bush, McKenry, & Wilson, 2003; Cui et al, 2014; Kunz & Grych, 2013; Silk, Steinberg, & Morris, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Magnusse (16) found that both adolescents and parental over-control are associated with higher levels of depressive symptoms. Some other studies found significant associations between parenting style and depression (12)(13)(14) . It is found that positive correlation exists between authoritarian parenting style and depression.…”
Section: Introductionmentioning
confidence: 98%
“…Human beings change and develop most dramatically during adolescence in the life cycle. Various biological, cognitive, emotional, and social changes that take placein adolescence and the parent-child relationship get affected by parenting styles (4,5) .Many studies have shown a link between parent-child interaction and emotional and behavioral adjustment in early childhood, middle childhood, and adolescence (14) . Therefore, it seems necessary to clarify which factors influence parenting styles in this particular period of life.…”
Section: Introductionmentioning
confidence: 99%